Peningkatkan Konsep Diri Positif Peserta Didik di SMP Menggunakan Konseling Individu Rational Emotive Behavior Therapy (REBT) - Thahir, Andi; Firdaus, Firdaus (Universitas Islam Negeri Raden Intan Lampung, 2017)
Positive self concept that arises in the counselee stems from the belief and positive piker pattern of the counselee to the ability and potential that he has. The results showed that the subjects had low self-concept. Low self-concept is shown include embarrassment with different physical circumstances, minder, do not want to ask the teacher if you do not understand, do not want to go forward, do not want to mingle with friends and, feel different from friends because always called as duck every talking. The purpose of this study is to change the client's irrational beliefs (which impact on emotions and behavior) to be irrational. Rational Emotive Behavior Therapy (REBT) aims to improve and change attitudes, perceptions, beliefs and views of irrational counselees to be rational, so that the counselee can develop themselves and achieve optimal self-realization. The type of research used in this study is a qualitative case study that is descriptive. Observation results show that after being given individual counseling service of Rational Emotive Behavior Therapy (REBT) technique there is a change, that the counselee is no longer embarrassed by his physical condition, going out of class to play, the counselee asks and forward the class, start accepting the shortcomings and try to optimize the potential there on him. The use of individual counseling techniques Rational Emotive Behavior Therapy (REBT) can help students in improving the concept of Positive Self